Efektivitas Minyak Atsiri dan Ekstrak N-Heksana Daun Beluntas sebagai Insektisida Alami dengan Bioindikator Ulat Hongkong: Efektivitas Minyak Atsiri dan Ekstrak N-Heksana Daun Beluntas sebagai Insektisida Alami dengan Bioindikator Ulat Hongkong - Juwita , Tita; Agustin, Nadia; Riris, Ida Duma; Eddiyanto; Hendrawan (Universitas Bangka Belitung, 2025)
Natural insecticides are pest control materials derived from natural sources such as plants. The use of natural insecticides is very important because it has a lower cost, is safe for living things and does not pollute the environment, so this study aims to determine the activity of essential oils and n-hexane extracts of beluntas leaves (Pluchea indica L.) as natural insecticides with bioindicators of Hong Kong caterpillars (Tenebrio molitor). Isolation of essential oils was carried out using the steam distillation method and extraction using the maceration method. Insecticide activity tests used the contact poison method and the residue method, with variations in extract and essential oil concentrations of 1%, 3%, 5%, 7%, 10%, 20%, 30% (v/v) and positive controls, namely Hippo insecticide and negative control tween 80. The results of the isolation of essential oils from beluntas leaves produced a yield of 2%, while extraction using the maceration method produced a yield of 1.84%. The results of the insecticide activity test using the contact poison method were more effective than the residue method. The insecticidal activity and n-hexane extract are more effective than essential oils, this is due to the differences in the content of secondary metabolite compounds contained in the extract and essential oil.